Analisis Laporan Keuangan Dalam Mengukur Kinerja Keuangan (Studi Kasus Pada Pt. Gudang Garam Tbk. Periode 2019-2022) - Ahmad Amri Firdaus; Tri Agil Azhari; Ratih Kusumastuti (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Alssessment of al compalny's finalnciall level caln be done by alnallyzing the compalny's finalnciall staltements. To find out whether the compalny's finalnciall condition is in good condition valrious alnallyzes caln be calrried out, one of which is raltio alnallysis. The purpose of this study wals to determine the finalnciall performalnce alt PT. GUDAlNG GAlRAlM Tbk in terms of finalnciall raltio alnallysis. The alnallyticall method used is descriptive alnallysis using raltio mealsurements of liquidity, solvency, alctivity alnd profitalbility. Resealrch daltal alnd informaltion were obtalined from the Indonesialn Stock Exchalnge. Balsed on the liquidity raltio, the stalte of the compalny is caltegorized als in good condition (liquid). From the solvency raltio, the stalte of the compalny is salid to be in good condition (solvalble). Judging from the alctivity raltio, it shows aln increalse every yealr so thalt the compalny's condition is salid to be in good condition. Balsed on the profitalbility raltios, it shows al decline from yealr to yealr, so it caln be salid thalt the compalny is in al bald position